Influence Of Admixtures On The Properties Of Extrudable Concrete For 3d Printing - Si, Kian Shen (Universiti Sains Malaysia, 2022)
The success of rapid industrialization in many parts of the world may be ascribed to automation techniques that resulted in a faster and less expensive production process. However, compared to other industrial sectors, the concrete building industry has not been as mechanised or to the same degree. In order to overcome this problem, three-dimensional printing (3DP) was first introduced in 1987. 3D printed concrete is a fabrication technology that uses an additive, layer-based manufacturing technique to create concrete components which requires less time and labour without the use of formwork. However, 3D printed concrete in construction industry of Malaysia is considered as a new technology. Thus, this experimental study will focus on the mechanical behaviour of 3D printed concrete and proposed a suitable mix proportion for 3D printed concrete. In this study, two main objectives were investigated: (a) Influence of admixtures toward the mechanical properties of 3D printed concrete, (b) the optimum mix proportion of 3D printed concrete. Five concrete mixes were prepared and tested based on workability, density, compressive strength, flexural strength and splitting tensile strength. Comparative study of mechanical properties of the 3DPC was done. Whereas prediction of optimum mix proportion for 3DPC was examined based on the properties of concrete. The results revealed that the mechanical properties of 3DPC improves with incorporation of silica fume without excessing the requirement. The optimum mix proportion for 3DPC was determined to be 3DPCS10 where the amount of the silica fume added was 10%.